Teacher training in innovative practices in higher education, using a MOOC: Preliminary Study - Laranjeiro, Dionísia (2022)
In this work we present a project that aims to develop a Massive Online Open Course (MOOC) for teacher training, promoting innovative pedagogical practices in higher education. The methodology adopted was Educational Design Research, which is presented in its fundamental characteristics. Focus is given to the preliminary literature review that served as theoretical framework for the project and helped in making the first development decisions. There are several recommendations and studies that argue the importance of using digital technologies in pedagogical activities, as well as using teaching and learning strategies centered on students- who increasingly use them in their learning. Some frameworks were also identified as guidelines for teacher training with digital technologies. The current pandemic context, which forced distance learning, reinforced the topicality of the theme, positioning MOOCs as good solutions for promoting innovative pedagogical practices in teacher training.